Definition and implementation of the Enterprise Business Layer through a Business Reference Model, using the architecture development method ADM-TOGAF - Carrillo, J. (2015)
Definition and implementation of the Enterprise Business Layer, is focused on strengthening the business architecture and IT governance. This work allows the company to define, and to be clear about the key elements of the business, also allows to establish the business baseline and the target business state. This work uses ADM-TOGAF v9. Based on this, the iteration of architectural capability of ADM has been tackled (Preliminary Phase and Architecture Vision), that has allowed the creation and evolution of the architectural capability required to start the exercise of enterprise architecture, this includes the establishment of an approach, principles, scope, vision and architectural governance. The architecture capability iteration serve as input for the first phase of the development iteration (Business Architecture), in which it has been performed the AS-IS and TO-BE analysis [1], which enables to establish the key points that should a company take to improve their current business scheme.